A portrait that asks questions: John Dempsey's 1828 painting John Rutherford, the Tattooed Englishman. Issue 1 (1st May 2019) - Bell, Leonard
Painted in England, John Dempsey's portrait (until recently attributed to George Scharf) represents John Rutherford, who lived in pre-colonial New Zealand from 1816 to 1826, with a full-face moko (tattoo), in European clothing and hat, smoking a pipe, with a basket of nuts slung over his left arm, and, curiously, holding a fortune wheel in his right hand. He is posed three-quarter length, facing the viewer. Rutherford was a Pākehā-Māori, a European who lived among Māori and was absorbed into the life of a tribe (Ngāpuhi). The circumstances of his time in New Zealand remain unclear. After leaving New Zealand, Rutherford claimed that he was a prisoner of Ngāpuhi and forcibly tattooed. Back in Britain, he enjoyed considerable mileage from this story, which was recounted in several publications. However, local accounts in New Zealand present a different story, of a man who willingly immersed himself in Māori culture and may well have played a primary role as a military strategist for Ngāpuhi in the widespread inter-tribal warfare of the period. He could be seen as a mediating figure, who crossed various boundaries between Māori and European, at a crucial time when the country was riven with internecine warfare among Māori, and proposals to colonize New Zealand were mooted. What role did Dempsey's portrait, an embodiment of transformation and multiple identifications, play in these dynamics? In what ways does the portrait convey the sense of a life? Or does it rather say something, inadvertently, about the Māori–European contact zone in a time of uncertainty, ambivalence and unknowability in their relationships? This article will explore these questions around this fascinating portrait.